2006
DOI: 10.1021/nl0608386
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polymer-Blend Morphology on Charge Transport and Photocurrent Generation in Donor−Acceptor Polymer Blends

Abstract: Monte Carlo algorithms are used to simulate the morphologies adopted by polymer chains in a polymer-blend film in the limits where the chains are mutually attractive (homophilic regime) and mutually repulsive (heterophilic regime) and then to simulate the drift transport of charges through the polymer chains. In the homophilic regime, chains aggregate into tangled domains resulting in a relatively high percolation threshold, a high density of configurational trap states, and slow, dispersive charge transport. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 27 publications
4
87
0
Order By: Relevance
“…1 shows that carrier mobility is improved when the domain size of the transporting component is increased, as would be expected. 12 When ␣ Ͼ 0.5, Fig. 1 shows that carrier mobility is reduced when the domain size of the nontransporting component is reduced.…”
Section: The Effect Of Morphology Upon Local Mobilitymentioning
confidence: 98%
See 1 more Smart Citation
“…1 shows that carrier mobility is improved when the domain size of the transporting component is increased, as would be expected. 12 When ␣ Ͼ 0.5, Fig. 1 shows that carrier mobility is reduced when the domain size of the nontransporting component is reduced.…”
Section: The Effect Of Morphology Upon Local Mobilitymentioning
confidence: 98%
“…This may be a serious deficiency in our knowledge, especially since the limited existing studies point to significant changes in charge transport when some aspects of morphology are changed. [12][13][14][15][16] In particular, Frost et al 12 showed that networks of self-repelling and self-attracting polymers show orders of magnitude difference in mobility and substantially different dispersive character.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 The influence of polymer-blend morphologies consisting of coiled polymer chains on charge transport and photocurrent generation in polymer blends has also been studied using Monte Carlo simulation methods. 15 Drift-diffusion modelling has also been successfully used to model organic solar cells. [16][17][18] However, such models are unable to take full account of the effect of three-dimensional structures, which are of interest here, instead reducing the complex morphology to a basic homogenous description or a simplified two-dimensional structure.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters in the transport equations can be estimated from quantum chemical calculations or experimental measurements (Coropceanu et al, 2007;Nelson et al, 2009;Westenhoff et al, 2006;. Such models of exciton and charge-carrier hopping between discrete sites have been used to study exciton and charge-carrier dynamics in BHJs, which can be simulated with a kinetic Monte Carlo algorithm (Frost et al, 2006;Groves et al, 2009;Meng et al, 2010;Watkins et al, 2005). These models can account for the molecular nature of the active layer, the morphology of the BHJ, and the anisotropy of exciton and charge transport in a straightforward fashion.…”
Section: Kinetic Monte Carlo Modelsmentioning
confidence: 99%
“…These models can account for the molecular nature of the active layer, the morphology of the BHJ, and the anisotropy of exciton and charge transport in a straightforward fashion. However, all implementations of such models so far (Frost et al, 2006;Groves et al, 2009;Meng et al, 2010;Watkins et al, 2005) have treated the dependence of the BHJ morphology on material properties and thermodynamic conditions in an approximate, albeit physically motivated, fashion: electron donor and acceptor sites were assumed to occupy sites on a cubic lattice and their interactions tuned to produce varying levels of phase separation after donor and acceptor sites were moved according to a Monte Carlo algorithm. Groves et.…”
Section: Kinetic Monte Carlo Modelsmentioning
confidence: 99%